Antagonistic Activity of Fungal Endophytes Isolated from Garcinia atroviridis against Colletotrichum gloeosporioides - Nur Afeeqah Binti Mohamed Zanudin; Nor'Aishah Hasan; Patahayah Binti Mansor (HAYATI Journal of Biosciences, 2020)
The extensive use of synthetic fungicides in controlling plant disease generates detrimental impacts on the environment and human health. In response to this problem, an alternative method was developed, known as biological control using antagonistic microorganisms. Since investigation on fungal endophytes of Garcinia atroviridis is still unclear, it was chosen for the study. The aim of the present work was to evaluate biocontrol potential of endophytic fungi against Colletotrichum gloeosporiodes, a phytopathogen that caused anthracnose disease. A total of 92 endophytic fungi were isolated from different tissue parts of Garcinia atroviridis including leaves, petioles, branches, and fruits. Results demonstrated that, most of endophytic fungal isolates showed some inhibitory action over the growth of C. gloeosporiodes during dual culture growth. Endophyte isolate F14 showed the highest antagonistic activity against Colletotrichum gloeosporiodes with 67.38% percentage inhibition radial growth (PIRG). However, 7 out of 92 isolates showed no inhibitory effect against Colletotrichum gloeosporiodes. In conclusion, endophytic fungi isolated from G. atroviridis indicate the potential as biocontrol agents. It is hoped that the finding of isolated endophytic fungi in this study with antagonistic activity against anthracnose pathogen may be used in biocontrol programmes of plant disease in the region.